An Impossible Encounter in the New intellectual History: Unbridgeable methodological Differences between the History of Ideas and Begriffgeschichte and the History of political languages. - Pizano, Alfredo (2025)
The new intellectual history is the result of the impact of the linguistic turn in historiography, which has been particularly welcomed in England, France and Germany. This turn conceals a barrier that prevents dialogue: while political language relies on speech acts as the key tool, for the history of concepts the long duration is situated in a complicated methodological framework, and both abandon the history of ideas. Thus, in this article I will expose the unbridgeable difference between the history of ideas of the Cambridge and Bielefeld schools.